2019
DOI: 10.3390/ma12010141
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis and In-Situ Measurement of Out-of-Plane Distortion in Thin Plate TIG Welding

Abstract: Transient distortion of thin plate in the welding process usually has a complicated mode and large magnitude. Quantitative measurement and prediction of full-field distortion are challenging and rarely reported up to now. In this study, the out-of-plane distortion of a thin plate during the Tungsten Inert Gas (TIG) welding process was measured using the digital image correlation (DIC) method. A simulation model based on thermal elastic–plastic finite element method (FEM) and DIC measured geometric imperfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…They concluded that the history of the material after forming had a considerable effect on the amount of residual stresses in the subsequent steps of the manufacturing process chain. Huang et al [13] reported similar results in Q235 steel, concluding that the initial distortions from forming can largely influence the buckling distortion during welding. Papadakis et al [14] studied the influence of preliminary manufacturing processes, i.e.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…They concluded that the history of the material after forming had a considerable effect on the amount of residual stresses in the subsequent steps of the manufacturing process chain. Huang et al [13] reported similar results in Q235 steel, concluding that the initial distortions from forming can largely influence the buckling distortion during welding. Papadakis et al [14] studied the influence of preliminary manufacturing processes, i.e.…”
Section: Introductionmentioning
confidence: 67%
“…The protruding areas exhibited larger deviations, e T5 similar to those after the forming process. The discrepancy between simulations and measurements in the final geometry of a welded component was analysed by Huang et al [13] in terms of the residual stresses present in the material from the rolling process. However, no residual stresses were assumed to be present in the material studied in this work prior forming.…”
Section: Resultsmentioning
confidence: 99%
“…The welding heat input is an important factor in forming weld deformations. It was stated by Huang et al [19], that the relationship between heat input and maximum deflection is not linear. There is a critical heat input beyond which the out-of-plane distortion starts to grow very quickly.…”
Section: Introductionmentioning
confidence: 98%
“…However, it can give rise to distortion known as longitudinal or buckling distortion due to the occurrence of the expansion process during the welding process and shrinkage when the weld begins to cool [ 14 ]. Over the last few decades, studies have developed several methods of planning and controlling this distortion [ 15 , 16 ]. In general, control of welding distortion and residual stresses can be accomplished using mechanical effects, thermal effects, or a combination of the two techniques and can be performed either during welding or after [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%